Norms emerge through iterated learning. - Partington, Scott; Kamtekar, Rachana; Nichols, Shaun (Proceedings of the National Academy of Sciences, 2025)
Injunctive norms are universal: Every culture has rules that specify what actions are forbidden, obligatory, or permitted. Where do all of these norms come from? In this paper, we identify a mechanism of cultural transmission that can explain the emergence of injunctive norms. In particular, we develop an iterated learning account that shows how weak biases in pedagogy and inference can drive norm emergence through cultural transmission. Using transmission chain studies, we confirm the core predictions of the iterated learning account. In five studies (N = 3,688), an initial generation of participants learn about an action that is merely inadvisable and teach a new generation of participants about that action. After this learning process repeats iteratively, participants in later generations reliably judge that the action is impermissible and subject to punishment. We find this inadvisable-to-impermissible effect is elicited across a wide range of initial conditions. Overall, then, our results support the idea that iterated learning can drive the emergence of injunctive norms across a wide range of contexts.
Peer reviewed: True
Publication status: Published
Keywords: cultural evolution; iterated learning; moral psychology; norms; Humans; Learning; Female; Male; Social Norms; Adult; Young Adult